Effects of subsidizing the firstemployee - Empirical evidence from Finland - Annika Nivala (Aboa Centre for Economics (ACE), 2019)
This paper studies the effects of a first employee wage subsidy imple-mented in parts of Finland in 2007â 2011 using the universe of Finnishfirms. The subsidy, amounting to 30% of the wage costs of the firstemployee in the first year and 15% in the second, was targeted to en-trepreneurs without hired employees. The target group accounts forover half of the firm population. Comparing the firms in the eligiblearea to firms in the neighboring ineligible area, I find precisely esti-mated zero effect on the probability of becoming an employer and otherfirm outcomes. The zero average effect seems to be due to low take-upof the subsidy highlighting the role of take-up in effectiveness of busi-ness subsidies. Sole proprietor, large and new firms were more likelyto use the subsidy and the subsidized firms seemed to grow more incomparison to eligible firms that did not use the subsidy.
Keywords: H25; H32; J23; J38; M51; 330; Business subsidies; Wage subsidies; Firm behavior; Labor demand; Entrepreneurship; Small Business